The company director's desktop guide - Martin, David M. (Thorogood Limited, 1998)
A guide to being an effective company director. The text includes sections on: directors' responsibilities; liabilities; leadership and management; handling board meetings; corporate governance; the role of the chairman and the company secretary; and working with shareholders